SUSTAINABLE DEVELOPMENT OF CITIES AND TERRITORIES: STRATEGIC DEVELOPMENT THEORY AND MEASUREMENT METHODOLOGY - Dmytro Anfilov (Соціальна економіка)
We aim to systematize the elements of sustainable development of cities and their social and ecological components in the theoretical and methodological basis of measuring the effectiveness of post-war reconstruction of the country. We study the theoretical and practical aspects of the economic growth of cities, and we systematize the components of implementing the strategy for achieving sustainable development of cities in the post-war period. We present the main characteristic features of the effective regional policy of the EU and Ukraine, highlighting the revitalization of polluted land plots in cities, the modernization of industrial facilities, the integrated regeneration of urban and rural areas, the development of environmentally friendly urban transport, and the development of residential construction.